(META)REFLEKSIVNI LIRSKI SUBJEKT I TIJELO: STILISTIČKA KONCEPTUALIZACIJA PJESNIČKE KNJIGE IPAK, ZORA TOMISLAVA AUGUSTINČIĆA. - Šunjić, Ivan (Croatica et Slavica Iadertina, 2024)
This paper examines the first poetry book by Tomislav Augustinčić, a contemporary Croatian theoretician, poet, and literary critic, entitled Ipak, zora (Still, Dawn). Analysis and interpretation are focused on the (meta)reflexive lyrical subject and body as the central thematic aspect of the book. The first part of the paper opens a question of this poetry book as a conceptual whole as well as its possible genre classifications, and chooses the genre mode – “long poem” or narrative poem – through which it is analysed and interpreted. In the second part of the paper, the focus in on the issue of the lyrical subject and/as a body, with an emphasis on time and space, intimistic and erotic (love) thematic scope, and metadiscursive relationships. In accordance with the theme of the journal in which it is published, the work is methodologically based on the contemporary stylistic reconceptualization of poetry and poetic style regarding the category of lyrical subject, poetic reflexivity, and imagery, as well as the metadiscursive poetic relations (Tin Lemac). The paper presents polydiscursiveness as a poetic and stylisticians constituent of this poetry book.